2017
DOI: 10.1515/ethemes-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Integrated AHP-TOPSIS Method for the Assessment of Health Management Information Systems Efficiency

Abstract: Abstract:The aim of this paper is to analyse and estimate the efficiency of health information systems in the provision of health care services. The evaluation of health information systems is conducted in the case of three most widely used softwares in the electronic health care. This evaluation is based on multi-criteria analysis of the health information systems efficiency using the AHP-TOPSIS method. This method, based on common attributes and their respective values for all three software solutions, indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…The authors found that TOPSIS methodology was applied successfully with many application domains. In [ 42 ], assessed the development of the best existing software solutions on the medical information systems' market by employing AHP-TOPSIS and reported that the best evaluated software isn't really the best for the usage and development. On the base of the eco‐environment, geographic and socio‐economic factors in Hunan province, the paper in [ 43 ] proposed a framework to select a site of inland NPPs of China by adopting many MCDM methods, however, the effectiveness of the TOPSIS was recommended in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that TOPSIS methodology was applied successfully with many application domains. In [ 42 ], assessed the development of the best existing software solutions on the medical information systems' market by employing AHP-TOPSIS and reported that the best evaluated software isn't really the best for the usage and development. On the base of the eco‐environment, geographic and socio‐economic factors in Hunan province, the paper in [ 43 ] proposed a framework to select a site of inland NPPs of China by adopting many MCDM methods, however, the effectiveness of the TOPSIS was recommended in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…of physicians, Total No. of professionals Public hospitals from 92 municipalities of Rio de Janeiro, for a period from 2008–2013 [ 40 ] -Vulnerability assessment of the health effects caused by climate variation -Validity of the vulnerability assessment results and the occurrence rate of cardiovascular patients Fuzzy TOPSIS Meteorological, air pollution, vulnerable group, vulnerable environment, disease distribution, socioeconomic-capacity, health/medical-capacity, air-pollution control Climate and air pollution data from South Korea in 2010 [ 41 ] Ranking variances between the TOPSIS and other MCDM approaches TOPSIS Combined-other-methods, year of publication, publication of journal, nationality of author 266 papers about TOPSIS applications published since 2000 in 103 journals of scholarly [ 45 ] Research priorities ranking for organization of military health AHP, TOPSIS Time priority, accordance with organizational goals, applicability and usefulness Cross-sectional study done in 2013 (clinics of a military health organization in Iran) [ 42 ] efficiency estimation of the health information systems in health care services and delivery AHP-TOPSIS Number of users of information systems Data redundancy Monthly growth of interoperability rates Rate of return on investment Monthly growing of the employment of data (big data) Valuation of compliance with HIPPA principles top 20 of the most used software solutions at the beginning of 2016 (from Electronic Health Record) [ 43 ] Selection of Power Plant Site of Inland Nuclear under Z‐numbers Z -number ‐BWM, Z -number ‐DEMATEL, and Z -number ‐TOPSIS Eco‐environment, physical geography, socio‐economics Hunan Province of China [ 44 ] Rank the hotel BEER projects ...…”
Section: Literature Reviewmentioning
confidence: 99%
“…TOPSIS method performs prioritization of alternatives based on their geometric distance from the positive-ideal and negative-ideal solution. Accordingly, it can be concluded that the best alternative will be the one with the shortest distance to the positive-ideal solution, and with the greatest distance from the negative-ideal solution (Rađenović & Veselinović, 2017). TOPSIS method involves the use of specific steps (Yoon & Hwang, 1995):…”
Section: Figure 1 Component Matrix Plotmentioning
confidence: 99%
“…The Technique for Order Performance by Similarity to Ideal Solution (TOPSIS), first proposed by Hwang and Yoon in 1981, is an MCDM widely used, in the presence of multiple and usually conflicting criteria, to evaluate and rank the performance of alternatives with respect to multiple criteria by similarity with the ideal solution [38].…”
Section: Topsismentioning
confidence: 99%
“…The main procedure of TOPSIS based on the geometric distance method representing ''closeness to the ideal'' is described in the following steps [38]: STEP T1. Build the normalized new decision matrix Y = [y i,j ] N a ×N c .…”
Section: Topsismentioning
confidence: 99%